Continuous Improvement of the Screen printing Process of Magnetic Sheets for Electric Machines by Statistical Design of Experiment - Schmidt, Alexander; Wieprecht, Nico; Thamm, Julian; Kühl, Alexander; Franke, Jörg (Lecture Notes in Mechanical Engineering, 2023)
Electric machines are an essential element to the electrification of industry and mobility for achieving a sustainable economy. Particularly important are the resource-efficient production of stator and rotor sheet packages and the reduction of iron losses during operation. The screen printing technology enables the production of very thin magnetic sheet laminations in near net shape geometry and thereby minimization of material waste in production. Simultaneously the efficiency of electric motors in use will be increased by reduced eddy current and hysteresis losses due to decreasing sheet thickness and avoided mechanical stress in the manufacturing process. In addition, screen printing enables multi-material components and variable alloy compositions. This paper presents the requirements of the screen printing process for magnetic sheets and identifies the relevant influencing factors and printing parameters to achieve the product specifications in multiple iterations and using universal statistical design of experiments methods. The target parameters investigated are cycle-time, green part weight, roundness, and layer thicknes
Keywords: Additive Manufacturing; Electric Motor; Magnetic Sheets; New Materials; Resource-efficient Production